2004
DOI: 10.1021/ic048607u
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-Tripodal Hydroxypyridonate Gadolinium Complexes:  Syntheses, Relaxometric Properties, Water Exchange Dynamics, and Human Serum Albumin Binding1

Abstract: The synthesis and relaxometric properties of hetero-tripodal hydroxypyridonate-terephthalamide gadolinium (Gd(3+)) chelates with differing structural features for probing human serum albumin (HSA) interactions are reported. The Gd(3+) complexes are divided into two series. The first series (3-5) features a benzyl derivative connected to the hydroxypyridonate (HOPO) moiety. The second series of complexes (6-10) has the common feature of a poly(ethylene glycol) (PEG) attached to the terephthalamide (TAM) moiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 25 publications
6
42
2
8
Order By: Relevance
“…Its lower than expected relaxivity is, therefore, a consequence of its lower number of inner sphere water molecule (q = 1). This deduction is in agreement with previous studies [26][27][28] that have demonstrated that long poly(ethyleneglycol) chains almost always displace one water molecule. Moreover, a significant contribution to the total relaxivity results from H-bonded water molecules in the proximity of the paramagnetic center.…”
Section: Relaxivity Of Gd(iii) Complexessupporting
confidence: 93%
See 1 more Smart Citation
“…Its lower than expected relaxivity is, therefore, a consequence of its lower number of inner sphere water molecule (q = 1). This deduction is in agreement with previous studies [26][27][28] that have demonstrated that long poly(ethyleneglycol) chains almost always displace one water molecule. Moreover, a significant contribution to the total relaxivity results from H-bonded water molecules in the proximity of the paramagnetic center.…”
Section: Relaxivity Of Gd(iii) Complexessupporting
confidence: 93%
“…The observed increase in relaxivity is consistent with previous reports of weak interactions between the small PEG chain and plasma proteins. [26][27][28] The adducts of the Gd(III) complex with the proteins behave as macromolecules which tumble significantly slower; the resulting longer τ R thus increases the relaxivity of the complex.…”
Section: Affinities For Physiological Anionsmentioning
confidence: 99%
“…[47] A key feature of this ligand design is the second amide functionality of the TAM that allows for further derivatization with solubilizing and targeting groups. [49,50] Relaxivities of Gd-HOPO and bis-HOPO-TAM complexes are generally in the range of 7 -13 mM -1 s -1 (20 MHz), and high complex stabilities combined with increased q and optimal water exchange rates make these compounds promising as safe, high-relaxivity agents at high field. The coordination chemistry and relaxometric properties of this class of compounds will be described in the following sections with emphasis on recent work published subsequent to a previous review.…”
Section: Hydroxypyridinone-based Agentsmentioning
confidence: 99%
“…A reduction in the hydration number for PEG-substituted complexes has also been observed in subsequent studies. [50] While complexes bearing chains of 11 and 12 ether units (23) exhibit relaxometric behaviour that suggests q = 1, [50,64] q remains 2 as in the parent compound when the chain is reduced to 4 ethers (25). These results indicate that a relatively short PEG chain is necessary to balance a high q value with water solubility.…”
Section: Effect Of Peg Substituentsmentioning
confidence: 99%
“…[68][69][70][71][72] Unfortunately, the side-chain carboxylate groups of the proteins, such as serum albumin, may cause a partial or total displacement of the coordinated water molecules of the bisand trisA C H T U N G T R E N N U N G (aquo) complexes, thus suppressing the relaxivity enhancement benefit as a result of the high number of these water molecules in the free complex. [9,10,66,73] The presence of hydrophobic pyridine groups on the dpaa ligand incited us to explore whether [GdA C H T U N G T R E N N U N G (dpaa) 3 ] complex and, in particular, its effect on the coordination environment of the gadolinium centre, we performed luminescence studies in the presence of BSA [74] and measured the water-proton longitudinal and transverse relaxivities in solutions of the gadolinium complex containing increasing BSA concentrations at 298 K and a proton resonance frequency of 60 MHz that correspond approximately to the imaging field of 1.5 T.…”
Section: H T U N G T R E N N U N G (Dpaa)a C H T U N G T R E N N U N mentioning
confidence: 99%